The effects of teacher competence on student outcomes in elementary science education: The mediating role of teaching quality. (November 2019) - Fauth, Benjamin; Decristan, Jasmin; Decker, Anna-Theresia; Büttner, Gerhard; Hardy, Ilonca; Klieme, Eckhard; Kunter, Mareike
Abstract: In this contribution, we investigate links between teacher competence, teaching quality, and student outcomes in elementary science education. Students' conceptual understanding and interest were measured during two teaching units in a pre-post design (1070 students, 54 classes). Results show that teacher competence (pedagogical content knowledge, self-efficacy, and teaching enthusiasm) was positively related to students' interest; self-efficacy was positively related to student achievement. Three dimensions of teaching quality (cognitive activation, supportive climate, and classroom management), which refer to the actual teacher-student-interactions in the classroom, mediated these relationships. These results help illuminate the mechanisms behind the effects of teachers on student outcomes. Highlights: We examined links between teacher competence, teaching quality, and student outcomes. Pedagogical content knowledge, self-efficacy, and teaching enthusiasm were positively related to students' interest. Self-efficacy was positively related to student achievement. Teaching quality in the classroom mediated these relationships.